PERANCANGAN PROMOSI ASIATUR TOUR DAN TRAVEL PADA MEDIA WEB DESAIN - AULANDA SATRIA UTAMA, Hendra Afriwan, S.Sn., M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Demand in transportation services such as travel in West Sumatera is increasing, so that the rivalry becomes strict. Every transportation service or travel bureau competes with each other to attract the consument's attention for that demand. It all can be seen from the tight rivalry on the service quality, price and promotion, among travel agency companies, there are some matters that are not fulfilled yet. One of them is the lack of promotion and the ineffectiveness of the information explained about the service or the tour package.Based on that problem, Web Design for Promotion of Asiatur Tour and Travel was made. In this design process, the writer used SWOT analysis method (strength, weakenesses, opportunity, threat). The writer did the analysis to the Web Design for Promotion of Asiatur Tour and Travel that has never been made before.As a revies on designing the web, it is supported with some media such as shirt, neck pillow, brochure, car branding, name card, and sticker which can promote the website of Asiatur Tour and Travel.Key Search: Promotion, Asiatur Tour and Travel, Web Design.